Personage Signature and Consumer Decision-Making in the Digital Marketplace: A Study of Smartphone Buyers in Nagpur - Smita Ramchandra Rao Gaikwad ,Dr.Anand Ashok Muley (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The study investigates the impact of Personage Signature on consumer decision makingprocess in the digital market focusing on the recipients (smartphone buyers) of Nagpur City.Key areas for Personage Signature are credibility, authenticity, attractiveness, expertise, personage– brand congruence and digital engagement are explored